2007
DOI: 10.5014/ajot.61.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned: A Pilot Study on Occupational Therapy Effectiveness for Children With Sensory Modulation Disorder

Abstract: A comprehensive program of research is needed, including multiple pilot studies to develop enough knowledge that high-quality effectiveness research in occupational therapy can be completed. Previous effectiveness studies in OT-SI have been single projects not based on a unified long-term program of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…It provides a systematic process for identification of goals that are specifically relevant to individuals and their families and has been shown to be a promising outcome measure in ASD (Ruble et al 2012). GAS has been used extensively for outcome measurement (Ruble et al 2010; Pfeiffer et al 2011; Miller et al 2007; Mailloux et al 2007) and is shown to be a valid and reliable method for measurement of progress on individualized goals for children with ASD (Ruble et al 2012; Palisano et al 1992). For example, Ruble et al (2012) report good reliability when objectives are clearly measurable finding average intra class correlation between 2 study samples of 0.98 (CI 0.74–0.99) for measurability, 0.96 (CI 0.74–0.99) for equi-distance, and 0.77 (CI 0.65–0.99) for difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…It provides a systematic process for identification of goals that are specifically relevant to individuals and their families and has been shown to be a promising outcome measure in ASD (Ruble et al 2012). GAS has been used extensively for outcome measurement (Ruble et al 2010; Pfeiffer et al 2011; Miller et al 2007; Mailloux et al 2007) and is shown to be a valid and reliable method for measurement of progress on individualized goals for children with ASD (Ruble et al 2012; Palisano et al 1992). For example, Ruble et al (2012) report good reliability when objectives are clearly measurable finding average intra class correlation between 2 study samples of 0.98 (CI 0.74–0.99) for measurability, 0.96 (CI 0.74–0.99) for equi-distance, and 0.77 (CI 0.65–0.99) for difficulty.…”
Section: Methodsmentioning
confidence: 99%
“…Goal Attainment Scaling (GAS; Schaaf & Nightlinger, 2007) quantifies goal progress in everyday life. Miller, Schoen, James, and Schaaf (2007) reported an interrater reliability of .67 with various populations. To use GAS, one identifies current behavior, creates incremental steps toward desired behavior, and then evaluates level of goal attainment at the conclusion of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…To use GAS, one identifies current behavior, creates incremental steps toward desired behavior, and then evaluates level of goal attainment at the conclusion of the intervention. Studies have indicated that GAS is an effective posttest measure for parents to report behavior change (Graham et al, 2010;Miller et al, 2007). For this study, parents identified goals and therapists coached parents in scaling them incrementally.…”
Section: Methodsmentioning
confidence: 99%
“…Sensory Integration is a theory, a model of assessment, and a form of therapy. Sensory processing disorders (Miller, Schoen, James, & Schaaf, 2007) is the proposed new definition, and an application has been made for it to be part of the DSM-V. This model of practice is used with a range of diagnostic groups including attention deficit hyperactivity disorder, DCD, autism spectrum disorder, learning disability, and mental health.…”
Section: Children's and Young People's Occupational Therapymentioning
confidence: 99%